KEWENANGAN INTERNATIONAL CRIMINAL COURT (ICC) TERHADAP PENYELESAIAN SENGKETA ROHINGNYA DI MYANMAR - adminjfh, adminjfh (Fakultas Hukum Universitas Selamat Sri, 2022)
The International Criminal Court (ICC) is a permanent tribune and authorized to prosecute individual perpetrators for international crimes that include genocide crimes, war crimes, aggression crimes and even crimes against humanity including ethnic crimes in Rohingnya. Where on the one hand also the Security Council (UNSC) also has the authority in taking action against crimes and reporting crimes in Rohingnya which include countries that are parties or countries that are not parties to the Rome Statute. Where the forms of crimes experienced by Rohingnya people in Myanmar are crimes that are handled by the Rome Statute in which the ICC does not have the authority to handle the case because Myanmar is not an ICC party country, but because Bangladesh is a country that is affected by the Rohingans porting, then Bangladesh has the right to report the case of Rohingnya in Myanmar to the UN Security Council. Where the UN Security Council is obliged to make and issue a letter of recommendation addressed to the ICC to conduct an investigation, prosecution of the case. This research was compiled using the method of library (library research) which was conducted by examining various secondary data sources in the form of books, journals, and other legal writings relating to the research topic. Also used normative methods that are descriptive in nature, the approach used is the legal approach, conceptual approach and legal principles approach. who reviewed and explained the issue of the International Criminal Court (ICC) Authority on the Resolution of Rohing Disputes in Myanmar.